Organ-tissue level of body composition and resting energy expenditure in Japanese college sumo wrestlers - Midorikawa, T.; Kondo, M.; Koizumi, K.; Kearns, C. F.; Abe, T. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Sumo wrestlers have the largest recorded fat-free body mass (FFM) in humans (121.3kg; Kondo 1994). Since FFM is major determinant of resting energy expenditure (REE), Sumo wrestlers have a high REE. However, recent studies have reported that FFM is not a single homogenous metabolic compartment. REE can be accurately calculated from organ-tissue mass in normal-weight subjects. Since Sumo wrestlers have a greater proportion of FFM, it is unknown whether they would have a similar pattern of organ-tissue mass relative to FFM. The purposes of this study were 1) to estimate organ-tissue level body compartments for heavyweight athletes (Sumo wrestlers) with a large FFM and 2) to investigate the relationship between the measured REE and the calculated REE from organ-tissue mass in Sumo wrestlers. Methods Four college Sumo wrestlers and four untrained students (controls) volunteered for the study. FFM was measured by two components densitometry. Skeletal muscle, brain, liver and kidneys volume was measured using magnetic resonance imaging (MRI) 1.5 T-scanners with spin-echo sequence. Contiguous MRI images with 1-cm slice thickness were obtained from the pileum to ankle joints. The volume of each organ-tissue was calculated from the summation of the digitized cross-sectional area. The individual organ-tissue volume data was converted into mass by an assumed constant density (Snyder 1975). Residual mass was calculated as the difference between body mass and the measured organ and tissue mass. REE was measured by indirect calorimetry. Gas exchange results were converted to REE in kcal/day using the Weir equation. The calculated REE was the sum of individual organ-tissue mass multiplied by their organ-tissue metabolic rate constants (Elia 1992). Results Sumo wrestlers had greater (p<0.01) body mass (103.1kg) and percent body fat (25.1%) than controls (63.1kg and 13.8%), but not standing height. FFM was greater in Sumo (77.4kg) than controls (54.3kg). Brain mass was similar between groups (Sumo 1.43 vs. controls 1.40kg). On the other hand, skeletal muscle, liver, kidney and residual mass in Sumo (35.7, 2.26, 0.47 and 33.1kg, respectively) were higher compared with controls (25.6, 1.29, 0.31 and 23.8kg). The ratio of muscle, kidneys and residual mass to FFM was similar between Sumo (45.7, 0.6 and 43.1%) and controls (47.7, 0.6 and 43.7%). The ratio of brain (Sumo 1.9 vs. controls 2.6%) and liver (2.9 vs. 2.4%) to FFM was different (p<0.05) between groups. The measured REE was similar to the calculated REE in both Sumo (2203 and 2243kcal/d, respectively) and controls (1511 and 1550kcal/d). There was strong correlation between the measured and calculated REE in Sumo (r=0.96. P<0.05) and in all subjects (r=0.97 P<0.01; Fig. 1). The ratio of the measured REE to FFM was similar between groups (Sumo 28.6 vs. controls 28.0 kcal/d/kg). Discussion/Conclusion It is unknown whether organ-tissue mass increases proportionally with increasing body or FFM. In Sumo wrestlers, FFM (largest FFM 90kg in this study) is composed of about 50% of skeletal muscle mass and another 50% of internal organ-tissue and residual mass. This was not different than the observed proportion in the untrained controls. Therefore, these data suggest that even with an extremely large body mass, the proportion of tissue components in FFM is relatively constant. It has been reported that REE can be accurately calculated from organ-tissue mass in normal-weight subjects. However, there are no published studies to confirm this approach for heavyweight athletes. In this study, there was a very strong agreement between the measured and calculated REE in Sumo wrestlers. Thus, the large REE in Sumo wrestlers (nearly 3000kcal/d) can be attributed to a larger absolute amount of high-metabolic organ-tissue mass including skeletal muscle, liver and kidneys mass.